Old Taoist : the life, art, and poetry of Kodōjin (1865-1944) - Addiss, Stephen, 1935-2022 (Columbia University Press, 2000)
In the literary and artistic milieu of early modern Japan the Chinese and Japanese arts flourished side by side. Kodojin, the "Old Taoist" (1865-1944), was the last of these great poet-painters in Japan. Portraying this last representative of a tradition of gentle and refined artistry in the midst of a society that valued economic growth and national achievement, this beautifully illustrated book includes a wide selection of his finest poems, paintings, and calligraphy